Mural calcifications in keratocystic odontogenic tumor: Report of a case with a brief review - Suhasini Gotur Palakshappa; Vijay Wadhwan; Preeti Sharma; Vishal Bansal (SRM Journal of Research in Dental Sciences, 2016)
Hard tissue deposits or mineralization in the wall of the keratocystic odontogenic tumor (KCOT) are infrequent and unusual. They are usually of dystrophic calcification or cartilage type, and dentinoid formation, although reported, is a rare phenomenon. Here, a rare case of extensive mural calcifications in the wall of the KCOT involving maxillary premolar-molar area, in a 14-year-old boy is described. These calcifications were found to be dentinoid, confirmed with the use of special stains.